2019
DOI: 10.1002/adfm.201908382
|View full text |Cite
|
Sign up to set email alerts
|

Salt‐Assisted Growth of P‐type Cu9S5 Nanoflakes for P‐N Heterojunction Photodetectors with High Responsivity

Abstract: P‐n junctions based on two dimensional (2D) van der Waals (vdW) heterostructure are one of the most promising alternatives in next‐generation electronics and optoelectronics. By choosing different 2D transition metal dichalcogenides (TMDCs), the p‐n junctions have tailored energy band alignments and exhibit superior performance as photodetectors. The p‐n diodes working at reverse bias commonly have high detectivity due to suppressed dark current but suffer from low responsivity resulting from small quantum eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 65 publications
0
55
1
Order By: Relevance
“…[ 41 ] Apparent reduction of Raman intensity called “Raman quench” indicated a strong interfacial coupling between the two flakes. [ 40,42,43 ] The Raman mapping of Bi 2 O 2 Se (159 cm −1 ) and WSe 2 (256 cm −1 ) (Figure 1f,g) further confirms the high‐quality of the heterostructure, exhibiting a great homogeneity of each component. We also collected the PL spectra from different areas (Figure 1e) and found no obvious PL signal was observed for bare Bi 2 O 2 Se due to the intrinsic indirect optical bandgap, [ 18,20 ] but strong excitonic emission around 775 nm of bare WSe 2 .…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…[ 41 ] Apparent reduction of Raman intensity called “Raman quench” indicated a strong interfacial coupling between the two flakes. [ 40,42,43 ] The Raman mapping of Bi 2 O 2 Se (159 cm −1 ) and WSe 2 (256 cm −1 ) (Figure 1f,g) further confirms the high‐quality of the heterostructure, exhibiting a great homogeneity of each component. We also collected the PL spectra from different areas (Figure 1e) and found no obvious PL signal was observed for bare Bi 2 O 2 Se due to the intrinsic indirect optical bandgap, [ 18,20 ] but strong excitonic emission around 775 nm of bare WSe 2 .…”
Section: Resultsmentioning
confidence: 57%
“…[ 37 ] On the contrary, when WSe 2 /Bi 2 O 2 Se heterostructure device operated under −5 V as shown in Figure 4c, the light on/off ratio enhanced to 618 (532 nm @ 52.37 mW cm −2 ) and a decent photoresponsivity of 638 mA W −1 (1.12 mW cm −2 ) in the WSe 2 /Bi 2 O 2 Se photodiode is also comparable to those of reported literature. [ 41,43,47,52,57 ] By fitting the light intensity ( P ) dependent I ph through the equation of I ph ∝ P α (Figure 4d), it was found that I ph at V ds = +5 V was relatively larger than 10 −6 A level with the α = 0.38, which indicated the existence of photogating effect and high photogain. [ 34 ] Therefore, the WSe 2 /Bi 2 O 2 Se heterostructure could operate as photodiode with high photoresponse and high sensitivity as the photoswitching characterization in Figure S6a,b, Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…The performance of self-powered MoS 2 photodetectors can be enhanced due to the piezoelectric effect. 221,258,272 MoS 2 based self-powered broadband photodetectors have been reported for n-MoS 2 /n-GaAs, 438 MoS 2 /b-Ga 2 O 3 , 439 Pd-MoS 2 /Si, 440 Pd/Al 2 O 3 /MoS 2 , 441 Pd/HfO 2 /MoS 2 , 441 graphene/InSe/MoS 2 , 442 p-Cu 9 S 5 /n-MoS 2 , 443 and MoS 2(1Àx) -Se 2x . 385,386,435 MoS 2 based self-powered photodetectors exhibit photoresponsivity from mA W À1 to A W À1 , detectivity from 10 9 to 10 15 Jones and response time from microseconds (ms) to seconds (s), depending on the measurement wavelengths and incident power densities which could be used for healthcare applications.…”
Section: Strain-induced and Self-powered Mos 2 Photodetectorsmentioning
confidence: 99%
“…The excellent recoverability of the CCF sensor make it suitable for attaching into the skin for continuous and long-term detection of an individual's motion. Furthermore, the elastic non-close-packed CCFs have a broad sensing range up to 68% strain, that is clearly higher than that of the recently reported elastic close-packed CCFs, [32] inverse opals film and organic CC gel, [33,34] and can satisfy the detection of large human motion, such as joint bending movements up to ≈55% strain. However, the CCF sensors exhibits no obvious, naked-eye visualized color change when the stretching strain is <10% (Figure 3a) and cannot satisfy the detecting subtle human motion, such as respiratory and pulse movements.…”
Section: Wwwadvmattechnoldementioning
confidence: 76%
“…Up to now, various flexible mechanochromic PCs including inverse opal colloidal crystal films (CCFs), colloidal particles embedded in elastomers have been developed for the visualized detection of strain. [32][33][34][35][36][37] However, for the practical application of PCs as mechanochromic sensors, these sensors are usually employed to detect large strain and cannot satisfy the detection of subtle strain because simple naked-eye detection of colorimetric changes require sufficiently large mechanochromic deformation of PCs that must be induced by the strain.…”
Section: Introductionmentioning
confidence: 99%